Kaempferia Sp. Extracts as UV Protecting and Antioxidant Agents in Sunscreen - Jukreera Panyakaew (2020)
© 2020, © 2020 Taylor & Francis Group, LLC. The ethanolic rhizome extracts of Kaempferia species (K. angustiflora, K. elegans, K. galanga-1, K. galanga-2, K. galanga-3, K. marginata, K. parviflora, K. pulchra, and K. rotunda) were evaluated for their UV protective and antioxidant properties. The effective extracts K. elegans, K. galanga-1, and K. parviflora were further isolated and 18 pure compounds were obtained. Flavokawain B (1), a chalcone found in K. elegans, exhibited the most effective UVA and UVB protection, and were more potent than commercial sunscreens. Compound 1 demonstrated the highest antioxidant activities in ABTS, DPPH, and FRAP assays. Abbreviations: ABTS: 2,2´-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid; DPPH (1,1-diphenyl-2-picrylhydrazyl); FRAP: ferric reducing antioxidant power; UV: Ultraviolet; UVA: Ultraviolet A; UVB: Ultraviolet B.